Bacterial Type II Secretion System and Its Mitochondrial Counterpart - Shaliutina-Loginova, Anna; Francetic, Olivera; Doležal, Pavel (mBio, 2023)
Over the billions of years that bacteria have been around, they have evolved several sophisticated protein secretion nanomachines to deliver toxins, hydrolytic enzymes, and effector proteins into their environments. Of these, the type II secretion system (T2SS) is used by Gram-negative bacteria to export a wide range of folded proteins from the periplasm across the outer membrane. Recent findings have demonstrated that components of the T2SS are localized in mitochondria of some eukaryotic lineages, and their behavior is consistent with the presence of a mitochondrial T2SS-derived system (miT2SS). This review focuses on recent advances in the field and discusses open questions concerning the function and evolution of miT2SSs.
Keywords: mitochondrial evolution; sekreční systém typu II; Bacterial Secretion Systems; protein secretion; Periplasm; protein transport; evolution; mitochondria; Bacterial Proteins; Gram-Negative Bacteria; Type II Secretion Systems; type II secretion system; bakteriální sekreční systémy; periplazma; T2SS; gramnegativní bakterie; bakteriální proteiny